TEMA DAN FAKTA-FAKTA CERITA DALAM NOVEL DARI TANAH HARAM KE RANAH MINANG KARYA UMMUKI - Astrid Widia Murni; Wachid Purwanto Eko Purwanto (PIKTORIAL : Journal of Humanities, 2019)
Novels are long essays of prose containing a series of stories of a person's life with those around him highlighting the character and nature of each actor. This research was conducted with a qualitative descriptive method. The object of this research is novel sentences which include themes and facts of the story. The data in this study are excerpts from Ummuki's Dari Tanah Haram ke Ranah Minang. The theme contained in the novel is "The struggle of a woman to face the bitter life". The flow used by the author is a back and forth flow. The characters that often appear are emotion, concern, and do not care. The setting contained in the novel includes the setting of time, setting, and setting. The setting of the place used such as in rooms, orphanages, and at Guyarat. The time setting is early evening, two o'clock in the morning and the setting of the atmosphere depicted is tense, emotional and alarming.Keywords: themes and facts of stories, novels Dari Tanah Haram ke Ranah Minang